1982
DOI: 10.1530/jrf.0.0660113
|View full text |Cite
|
Sign up to set email alerts
|

Increased fertility in young primiparous female bank voles, Clethrionomys glareolus, treated with prolactin or progesterone after mating

Abstract: Fertility in young primiparous female bank voles was improved by daily injections after mating of progesterone (0\m=.\5mg/day) or prolactin (8 i.u./day).Prolactin treatment increased the number of healthy corpora lutea. The results suggest that the sterile matings at the start of the breeding season are not due to failure of ovulation, but to lack of progesterone from inactive CL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The females with placental scars evidently had had corpora lutea which were active enough to initiate implantation. Infertility in young female bank voles is due to lack of activation of the corpora lutea (Westlin & Nyholm, 1982;Westlin, 1982b). Because the above 5 females all showed evidence of activation of the corpora lutea, they were considered to have had fertile matings.…”
Section: Day 40 To 60 Of Agementioning
confidence: 99%
See 1 more Smart Citation
“…The females with placental scars evidently had had corpora lutea which were active enough to initiate implantation. Infertility in young female bank voles is due to lack of activation of the corpora lutea (Westlin & Nyholm, 1982;Westlin, 1982b). Because the above 5 females all showed evidence of activation of the corpora lutea, they were considered to have had fertile matings.…”
Section: Day 40 To 60 Of Agementioning
confidence: 99%
“…Treatment of recently mated females with progesterone increases fertility to 100% without activating the corpora lutea. The activation of corpora lutea is dependent on prolactin : injections of exogenous prolactin result in activation of corpora lutea and dramatically increase fertility (93% compared to 35% in untreated young females) (Westlin, 1982b). It is possible that sterile matings may prime the females and thus increase fertility of subsequent matings.…”
Section: Introductionmentioning
confidence: 99%
“…The present results would suggest that one contribution to the rise in fertility might be an increased sensitivity of the endometrium to the presence of blastocysts. However, this does not rule out the possibility that there is a change with age in the luteotrophic response to copulation (Westlin, 1982;Westlin & Gustafsson, 1984), although this has not been investigated experimentally.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that this is due to deficient output of progesterone by the ovaries, attributed to insufficient release of luteotrophin (Westlin, 1982). It has been supposed that either the threshold stimulus arising from mating and required to activate the luteotrophic complex is higher in young females than the satiety point of copulation for males, or that young females do not allow mating to satiety (Westlin & Gustafsson, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Young female bank voles frequently fail to become pregnant at their first matings. This occurs if the stud male is left with the female (Westlin & Nyholm, 1982) as well as if the stud male is removed and the female kept alone (Westlin, 1982b). Young females may have higher requirements for vaginal stimulation to activate the luteotrophic complex and one explanation for their lower fertility could be that the stimulus threshold for activation is seldom reached.…”
Section: Introductionmentioning
confidence: 99%